The Role of the IGF-1 Signaling Cascade in Muscle Protein Synthesis and Anabolic Resistance in Aging Skeletal Muscle - Barclay, Richie D.; Burd, Nicholas A.; Tyler, Christopher; Tillin, Neale A.; Mackenzie, Richard W. (Frontiers in Nutrition, 2019)
Sarcopenia is defined as the combined loss of skeletal muscle strength, function and/or mass with ageing. This degenerative loss of muscle mass is associated with poor quality of life and early mortality humans. The loss of muscle mass occurs due to acute changes in daily muscle net protein balance (NPB). It is generally believed a poor NPB occurs due to reduced muscle protein synthetic responses to exercise, dietary amino acid availability, or an insensitivity of insulin to suppress breakdown. Hence, ageing muscles appear to be resistant to the anabolic action of exercise and protein (amino acids or hormonal) when compared to their younger counterparts. The mechanisms that underpin anabolic resistance to anabolic stimuli (protein and resistance exercise) are multifactorial and may be partly driven by poor lifestyle choices (increased sedentary time and reduced dietary protein intake) as well as an inherent dysregulated mechanism in old muscles irrespective of the environmental stimuli. The insulin like growth factor 1 (IGF-1), Akt /Protein Kinase B and mechanistic target of rapamycin (mTOR) pathway is the primary driver between mechanical contraction and protein synthesis and may be a site of dysregulation between old and younger people. Therefore, our review aims to describe and summarise the differences seen in older muscle in this pathway in response to resistance exercise (RE) and describe approaches that researchers have sought out to maximise the response in muscle. Furthermore, this review will present the hypothesis that inositol hexakisphosphate kinase 1 (IP6K1) may be implicated in IGF-1 signalling and thus sarcopenia, based on recent evidence that IGF-1 and insulin share some intracellular bound signalling events and that IP6K1 has been implicated in skeletal muscle insulin resistance.